Developments in transcatheter tricuspid valve therapies. (2nd December 2019) - Voci, Davide; Pozzoli, Alberto; Miura, Mizuki; Gavazzoni, Mara; Gülmez, Gökhan; Scianna, Salvatore; Zuber, Michel; Maisano, Francesco; Taramasso, Maurizio
ABSTRACT: Introduction : Transcatheter tricuspid valve (TV) procedures emerged as an alternative to surgery for symptomatic high-risk patients with severe tricuspid regurgitation. Areas covered : A literature search was performed using PubMed. Authors review clinical evidence in this field, the imaging features and the developments in TV transcatheter technologies. Currently, transcatheter devices for TV procedures can be allocated into four main groups: 1) those ones targeting leaflet malcoaptation, 2) those addressing annular dilatation, 3) those performing heterotopic valve implantation and 4) those onesaccomplishing a complete transcatheter replacement of the valve. Expert opinion : Actually, encouraging results are provided by initial experience in the field of transcatheter TV procedures. However, this field remains full of challenges that faced could lead to better results and prognosis for the patients. The next steps in this emerging field will need to focus on accurate patient selection, an early patient referral and on studies comparable and providing long-term data.